2013
DOI: 10.1111/jiec.12017
|View full text |Cite
|
Sign up to set email alerts
|

Business‐to‐Business Information Technology User Practices at End of Life in the United Kingdom, Germany, and France

Abstract: Summary Business‐to‐business (B2B) electronics account for a significant volume of the electrical and electronic equipment (EEE) put on the market. Very little B2B waste electrical and electronic equipment (WEEE) is reported as collected in the European Union (EU) in compliance with the WEEE Directive, which uses the policy principle of extended producer responsibility (EPR) to ensure that WEEE is managed correctly. This presents a barrier to parties looking for access to the waste. Company practice dictates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The re-use sector for EEE has grown steadily over the last decades; however, there is still a lot of latent potential (Babbitt et al, 2011;Kissling et al, 2012;Peagam et al, 2013). Generic re-use operating models for EEE as well as success factors and barriers in re-use of EEE have recently been investigated by Kissling et al (2012Kissling et al ( , 2013.…”
Section: Life Time Extension Of Eeementioning
confidence: 99%
See 2 more Smart Citations
“…The re-use sector for EEE has grown steadily over the last decades; however, there is still a lot of latent potential (Babbitt et al, 2011;Kissling et al, 2012;Peagam et al, 2013). Generic re-use operating models for EEE as well as success factors and barriers in re-use of EEE have recently been investigated by Kissling et al (2012Kissling et al ( , 2013.…”
Section: Life Time Extension Of Eeementioning
confidence: 99%
“…Barriers related to regulations, standards, product design and costs were identified as well. (Kissling et al, 2013) For improving the access to sufficient volumes of good quality EOL EEE, the studies of Babbitt et al recycling and refurbishment of B2B ICT devices at the end of use seem to be commonplace in the EU (Peagam et al, 2013). The study of Peagam et al (2013) also showed that the majority of devices reached their EOL after 3 to 4 years or in 3 years if the units had fixed replacement periods.…”
Section: Life Time Extension Of Eeementioning
confidence: 99%
See 1 more Smart Citation
“…The time laps between selling EEE and the collection of WEEE cannot justify these results. According to Peagam et al (2013), very little business-to-business WEEE is reported as collected in Europe. Italy reported to Eurostat that around 5 kg per capita of WEEE are collected from sources other than households: the highest among EU countries (average 0.6 kg in 2012).…”
Section: Technical Performancementioning
confidence: 98%
“…In “Business‐to‐Business Information Technology User Practices at End‐of‐Life in the United Kingdom, Germany, and France,” Peagam and colleagues () provide an empirical study targeted at (1) understanding the end‐of‐life characteristics of business‐to‐business (B2B) information technology (IT) product markets, and (2) determining the challenges associated with the collection and recycling of such products under the scope of EPR mandates such as the WEEE Directive of the European Commission. They describe a survey of commercial users of IT equipment in the United Kingdom, France, and Germany regarding the users’ end‐of‐life management of WEEE.…”
Section: Extended Producer Responsibility and Waste Electrical And Elmentioning
confidence: 99%